Linear Versus Volcano Correlations for the Electrocatalytic Oxidation of Hydrazine on Graphite Electrodes Modified with mn4 Macrocyclic Complexes - Zagal-Moya, J; Zagal-Moya, J; Recio-Cortes, F; Recio-Cortes, F; Tasca-Gottardo, F; Tasca-Gottardo, F; Venegas-Toledo, R (Elsevier Ltd, 2014)
For electrochemical reactions catalyzed by electrodes modified with MN4 macrocyclic transition metal complexes, it is commonly accepted that d-band vacancy, surface lattice strain, and eg-orbital filling the transition metals are essential parameters to take in account for an optimum catalysis. These parameters affect the formal potential of the catalyst which is related to the free energy of the adsorption of the reacting molecule to a point that volcano correlations have been reported when plotting the activity of the catalyst versus the Mz+/M(z-1)+ formal potential of the catalyst (M (II) = Fe, Co). The highest catalytic activity is achieved when the formal potential of the catalyst is close to -0.5 V vs SCE regardless of whether the central metal is Fe or Co. In this work, we review the work done until now on the oxidation of hydrazine in alkaline medium at metallophthalocyanines modified graphite electrodes and we show that for some complexes the redox potential of the MN4 macrocyclic transition metal complex can be varied changing the concentration of the catalyst at the electrode surface. Therefore we show that if log i (normalized for the actual surface concentrations of M(II) active sites (M = Fe, Co) at constant potential is plotted versus the M(II)/(I), the correlations is linear with a slope close to 2RT/F. © 2014 Elsevier Ltd.